The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00276-020-02644-y
|View full text |Cite
|
Sign up to set email alerts
|

Global incidence of spinal perineural Tarlov’s cysts and their morphological characteristics: a meta-analysis of 13,266 subjects

Abstract: Background Spinal perineural Tarlov’s cysts (TCs) are considered incidental findings that occasionally might exert pressure upon nerve roots and correspond with patients’ signs and symptoms. Purpose of this meta-analysis is to deliver global incidence and characteristics (location, size, and shape) of TCs. Methods Following PRISMA checklist, all major databases were searched by two authors for radiologic studies reporting incidence and morphologic features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…Lim et al 32 found a discordant relationship between TCs and pudendal neuralgia. In a meta-analysis of 22 radiological studies, Klepinowski et al 33 found a correspondence with symptoms in only 16% of TCs.…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al 32 found a discordant relationship between TCs and pudendal neuralgia. In a meta-analysis of 22 radiological studies, Klepinowski et al 33 found a correspondence with symptoms in only 16% of TCs.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 1% of perineural cysts are symptomatic due to compression or stretching of the adjacent nerve roots [ 12 , 15 , 16 ]. However, Tarlov cysts can slowly increase in size over time and cause significant bone scalloping [ 17 ]. Their propensity to attenuate the mechanical endurance of the sacrum is seen in cases complicated with insufficiency fractures reported in young patients [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Although symptomatic TCs can present with neurological symptoms such as sciatica, low back pain, lower extremity paresis, dyspareunia, and bladder/rectal disturbance, 8 the majority are asymptomatic and found by chance via magnetic resonance imaging (MRI) and computed tomography (CT) examinations performed for various lumbosacral symptoms. 4,10 Natural or artificial rupture of TCs has been reported to prompt symptom changes, including rapid deterioration of related symptoms. [11][12][13] Although some researchers have reported the presence of TCs in pregnancy and delivery, 2,14,15 the impact of vaginal delivery on presacral TCs has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…TCs grow slowly, rarely extend to the endopelvic space, and seldom show natural regression 7–9 . Although symptomatic TCs can present with neurological symptoms such as sciatica, low back pain, lower extremity paresis, dyspareunia, and bladder/rectal disturbance, 8 the majority are asymptomatic and found by chance via magnetic resonance imaging (MRI) and computed tomography (CT) examinations performed for various lumbosacral symptoms 4,10 …”
Section: Introductionmentioning
confidence: 99%